Exploring the antecedents of high mobility among ship officers: empirical evidence from Australia. Issue 1 (2nd January 2021) - Divine Caesar, Livingstone; Cahoon, Stephen; Fei, Jiangang; Sallah, Cynthia Ayorkor
ABSTRACT: Since the publication of the first BIMCO/ISF Manpower update in 1990, research on HR issues in the global shipping industry has received increased attention from academics and practitioners. The relatively recent half a decade update which was published in 2015 predicts a potential global shortage of almost 147, 500 ship officers. With high mobility among ship officers to landside jobs emerging as one of the key contributory factors to the shortage, a more profound understanding of the antecedents of this ship-to-shore career movement is needed. Questionnaires were sent via web-based survey to 305 ship officers within the Australian shipping industry; with 198 responses received. The empirical results showed the factors that predict turnover among ship officers as organisational, extrinsic, personal and industry issues. Personal issues such as separation from family and home are the key reasons for the increased movement to shore-side jobs among ship officers. Further, a complex web of unaddressed retention issues may coerce officers to quite working onboard ships.